THE INFLUENCE OF MOTIVATION, JOB SATISFACTION AND LEADERSHIP STYLE ON TEACHER PERFORMANCE AT THE BUDI MULIA COLLEGE FOUNDATION - Tiara Dwi Mauliddyna; Rita Agusniat Larosa; Fichri Alfisyahri; Glen Bagasta Simanjuntak; Debora Tambunan; Ahmad Rivai (Universitas Efarina, 2024)
Abstract This study aims to analyse the effect of motivation, job satisfaction and leadership style on teacher performance at Yayasan Perguruan Budi Mulia. This study uses a quantitative method with a survey method involving 35 teachers as respondents. The data was analysed using multiple linear regression to determine the relationship between these variables. The results showed that motivation has a positive and significant effect on teacher performance, this can be seen from the motivation number (0.005) which is smaller than the 5% alpha (0.05) ortcount = 3.001> ttable 2.039. The research results of the job satisfaction variable have a positive and significant effect on teacher performance, judging from the number, namely the job satisfaction variable (0.014) is smaller than alpha 5% (0.05) ortcount = 2.594 > ttable 2.039, and leadership style shows a positive and significant influence on teacher performance, this can be seen from the number of leadership style variables (0.000) is smaller than alpha 5% (0.05) ortcount = 7.076 > ttable 2.039. This finding indicates that increasing motivation, job satisfaction and appropriate leadership style can improve teacher performance. Then the output results obtained from the coefficient of determination (adjusted R Square) are 0.694. So it can be seen that there is an influence of motivation variables, job satisfaction and leadership style on teacher performance by 69.4% and is influenced by other factors that affect teacher performance by 30.6%.